Beginning ArcGIS for Desktop Development Using . NET - Amirian, Pouria (Wrox programmer to programmer, 2013)
Get the very most out of the ArcGIS for Desktop products through ArcObjects and .NET ArcGIS for Desktop is a powerful suite of software tools for creating and using maps, compiling, analyzing and sharing geographic information, using maps and geographic information in applications, and managing geographic databases. But getting the hang of ArcGIS for Desktop can be a bit tricky, even for experienced programmers. Core components of ArcGIS platform is called ArcObjects. This book first introduce you the whole ArcGIS platform and the opportunities for development using various programming languages. Then it focuses on ArcGIS for Desktop applications and makes you familiar with ArcObjects from .NET point of view. Whether you are an ArcGIS user with no background in programming or a programmer without experience with the ArcGIS platform, this book arms you with everything you need to get going with ArcGIS for Desktop development using .NET?right away. Written by a leading expert in geospatial information system design and development, it provides concise, step-by-step guidance, illustrated with best-practices examples, along with plenty of ready-to-use source code. In no time you?ll progress from .NET programming basics to understanding the full suite of ArcGIS tools and artefacts to customising and building your own commands, tools and extensions?all the way through application deployment. Among other things, you?ll learn to: Object-Oriented and Interface-based programming in .NET (C# and VB.NET) Finding relationship between classes and interfaces using object model diagrams Querying data Visualizing geographical data using various rendering Creating various kinds of Desktop Add-Ins Performing foreground and background geoprocessing Learn how to improve your productivity with ArcGIS for Desktop and Beginning ArcGIS for Desktop Development Using .NET